Perceived home is associated with psychological well-being in a cohort aged 67–70 years. (August 2017) - Kylén, Maya; Schmidt, Steven M.; Iwarsson, Susanne; Haak, Maria; Ekström, Henrik
Abstract: Research on very old people has shown that perceived aspects of home are important for health, but research on such associations in younger cohorts of older people is lacking. The aim of this study was to investigate whether perceived aspects of home were associated with psychological well-being among community-living people aged 67–70. Interview data were collected with 371 individuals living in ordinary housing in southern Sweden. Statistical analyses revealed that depression was less common among participants who reported cognitive-emotional and social bonding to the home, and among those who felt that they had control over their housing situation. The behavioral, social and physical aspects of meaning of home as well as external control beliefs were associated with psychological well-being. Showing that perceived aspects of home are relevant for psychological well-being among people aged 67–70, this study adds to the knowledge on home and health dynamics during the ageing process. Highlights: Depressive mood and purpose in life are associated with a low control of home. Depressive mood is associated with low emotional and social attachment to home. High behavioural meaning of home is associated with feeling autonomous. The physical and social experience of home is associated with purpose in life. Perceptions about home must be considered when planning age-friendly communities.